Nonlinear Physiological Model of Insulin-Glucose Regulation System in Type 1 Diabetes Mellitus - Ali, Ahmed Mohammed; Tahir, Fadhil Rahma (Iraqi Journal for Electrical and Electronic Engineering, 2019)
Mathematical modeling is very effective method to investigate interaction between insulin and glucose. In this paper, a new mathematical model for insulin-glucose regulation system is introduced based on well-known Lokta-Volterra model. Chaos is a common property in complex biological systems in the previous studies. The results here are in accordance with previous ones and indicating that insulin-glucose regulating system has many dynamics in different situations. The overall result of this paper may be helpful for better understanding of diabetes mellitus regulation system including diseases such as hyperinsulinemia and Type1 DM.